Developments in tandem micro-machining processes to mitigate the machining issues at micron level: a systematic review, challenges and future opportunities - Sharma, Sahil; Singh, Tarlochan; Dvivedi, Akshay (Machining science and technology, 2022)
The requirement to fabricate the micro features in difficult-to-machine materials has increased the demand for new micro-machining processes. Over the years, various micro-machining processes have emerged, such as non-conventional, hybrid, and tandem micro-machining processes. Recently, among all of these processes, the tandem micro-machining processes have gained substantial attention. In these processes, two machining methods are arranged tandemly to mitigate the drawbacks of the primary one. This manuscript presents a comprehensive systematic review of the recent developments carried out in the novel tandem micro-machining processes. After conducting a literature review, the existing tandem micro-machining processes have been classified into four categories: Thermo plus Electrochemical, Thermo plus Mechanical, Thermo plus Thermo, and Hybrid plus Mechanical/Thermal. This work includes a detailed description of process conceptualization, process mechanisms, current development and capabilities of tandem micro-machining processes regarding work material and machined features. The manuscript's originality illustrates how combining two processes could effectively produce intricate shapes in difficult-to-cut materials. Furthermore, the various steps involved in developing a tandem process from the idea formulation to the implementation stage have been discussed in the manuscript. The future opportunities in tandem micro-machining processes have also been identified and presented as research potential. While motivated by the systematic investigation, initial experimental results obtained from the in-house developed micro tandem machining processes such as W-EDM plus W-ECM and Laser plus W-ECM have also been included.